2020
DOI: 10.1101/2020.01.28.923557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacodynamic Markers of LRRK2 Inhibition in Biofluids

Abstract: AbstractHyper-activated LRRK2 is linked to Parkinson’s disease susceptibility and progression. Quantitative measures of LRRK2 inhibition, especially in the brain, may be critical in the clinical development of successful LRRK2-targeting therapeutics. In this study, three different brain-penetrant and selective LRRK2 small-molecule kinase inhibitors (PFE-360, MLi2, and RA283) were orally administered to groups of cynomolgus macaques at different doses. Biofluid markers with prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…However, this phospho-to-total measure would be confounded in cases where total protein levels become low due to inhibitor treatment. A recent study evaluating LRRK2 inhibitors in non-human primate biofluids found that LRRK2 protein is unchanged in brain tissue but is diminished at varying levels in the periphery following acute treatment (Wang et al, 2020).…”
Section: Lrrk2 Regulation In Biomarker Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this phospho-to-total measure would be confounded in cases where total protein levels become low due to inhibitor treatment. A recent study evaluating LRRK2 inhibitors in non-human primate biofluids found that LRRK2 protein is unchanged in brain tissue but is diminished at varying levels in the periphery following acute treatment (Wang et al, 2020).…”
Section: Lrrk2 Regulation In Biomarker Responsesmentioning
confidence: 99%
“…Studies using acute drug dosing strategies and kinase-dead LRRK2 mutants have provided evidence that the subcellular localization of LRRK2 is altered and reductions in kinase activity can lead to LRRK2 protein destabilization and degradation. A recent study in non-human primates showed that acute dosing with structurally distinct LRRK2 kinase inhibitors PFE-360 or MLi2 reduces total LRRK2 detection within exosomes isolated from urine and cerebral spinal fluid (CSF) (Wang et al, 2020). Additionally, there is evidence that LRRK2 kinase activity is crucial for maintaining steady-state levels of LRRK2.…”
Section: Lrrk2 Regulation In Biomarker Responsesmentioning
confidence: 99%
See 1 more Smart Citation